Pemahaman Mahasiswa PAI terhadap Mata Kuliah Kesehatan Mental Studi Kasus STAI Al-Gazali Soppeng - Zahra Istiqamah (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to examine the conceptual understanding of second-semester students in the Islamic Religious Education program at STAI Al-Gazali Soppeng regarding the mental health course. A descriptive qualitative approach was used, with data collected through observation, interviews, oral tests, weekly quizzes, and video-based assignments. The results indicate that the majority of students demonstrated a good to excellent understanding of basic mental health concepts, as reflected by an average oral test score of 90. Students were also able to integrate Islamic values such as patience (sabr), gratitude (shukr), and trust in God (tawakkul) in addressing contemporary mental health issues. Weekly quizzes proved effective in enhancing engagement, content retention, and students’ reflective thinking. Additionally, video-based projects encouraged creativity, critical thinking, and the ability to contextualize course content in real-life situations. These findings suggest that active and contextual learning strategies significantly improve students’ conceptual understanding. The study recommends the wider adoption of similar approaches in teaching courses that incorporate Islamic values to foster awareness of the importance of mental health in students’ spiritual and social lives.